2018
DOI: 10.1021/acs.joc.7b02780
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Stille Cross-Couplings Using Mn(II)Cl2

Abstract: Cross-coupling reactions are a staple in organic synthesis, especially for C-C bond formation with sp- and sp-carbon electrophiles. In recent years, the range of accessible C-C bonds has been extended to stereogenic centers which expedites access to greater molecular complexity. However, these reactions predominantly depend upon late transition metal (LTM) catalysts whose cost, toxicity, and/or environmental impact have come under increasing scrutiny and governmental regulation. Here, we report Mn(II)Cl comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Then, the preference observed for oxidative addition of vinyl–I over Ar–I bonds to gold prompted us to explore the possibility to achieve chemoselective catalytic transformation of the difunctional substrate 4f featuring both vinyl–I and aryl–I moieties. 21 Pleasingly, using 1 eq. of 4-penten-1-ol or N -tosyl 4-penten-1-amine, the oxy- and amino-vinylations are largely predominant.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the preference observed for oxidative addition of vinyl–I over Ar–I bonds to gold prompted us to explore the possibility to achieve chemoselective catalytic transformation of the difunctional substrate 4f featuring both vinyl–I and aryl–I moieties. 21 Pleasingly, using 1 eq. of 4-penten-1-ol or N -tosyl 4-penten-1-amine, the oxy- and amino-vinylations are largely predominant.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty years later, Falck disclosed a report on the Mn-catalyzed stereospecific Stille crosscoupling in the reaction of protected α-alkoxy(tri-n-butyl)stannanes with organic electrophiles (Scheme 20) [22]. The MnCl2/(S)-BnCH2PyBOX system, employed in 50 mol%, mediated the coupling of various aryl iodides bearing electron-rich or electron-withdrawing groups and even heteroaryl iodides with the organostannanes (Scheme 20a).…”
Section: Mn-catalyzed Stille Cross-coupling Reactionsmentioning
confidence: 99%
“…In order to improve the reaction kinetics, it was found that a mixture of MnCl2 (15 mol%) with Cu(OTf)2 (20 mol%) and Jackphos (15 mol%) as ligand was superior to the Mn/Pybox-only system. Addition of KF and K3PO4 provided cleaner products under overall significantly faster and milder conditions (6-24 h, room temperature) (Scheme 21) [22].…”
Section: Mn-catalyzed Stille Cross-coupling Reactionsmentioning
confidence: 99%
“…Whereas inclusion of an α-oxygen substituent on a secondary alkyltin nucleophile is an effective strategy for promoting selective alkyl transmetallation, 3,39,40 far fewer examples of activation via an α-nitrogen substituent have been demonstrated. 13,18,19,41 This possibly arises from the lower electronegativity of nitrogen, which results in a muted propensity to promote alkyl transfer.…”
Section: Development Of a General Cross-coupling Reaction Employing αmentioning
confidence: 99%